Media Competencies in the Communication of Faith in Pope Francis’ Messages for World Communications Day (2014–2025) - Chmielewski, Mirosław (Verbum Vitae, 2025)
The article offers partial results of research on media competencies in the communication of faith, reconstructed on the basis of Pope Francis’ Messages for the World Communications Day (2014–2025). The research problem focuses on identifying the competencies deemed essential for the Christian proclamation within the digital culture and on analysing their theological and anthropological grounds in the face of such contemporary challenges as disinformation, social polarisation, and the development of artificial intelligence. A three-stage qualitative content analysis (exploration— categorisation—interpretation) was supported by contextual validation through comparison with the relevant literature and the teaching of the Church. The analysis helped to define five equivalent categories of media competencies: cognitive, ethical, relational, technical, and spiritual (each with four subcategories). This article discusses the first two of them, i.e. cognitive competencies (related to the search for truth, critical discernment, and reflection) and ethical competencies (responsibility, the culture of encounter, the ethics of technology, resistance to disinformation). Their mutual complementarity and deep grounding in Christian anthropology and Francis’ theology of communication were demonstrated. The messages show communication of the faith as an act of love, witness, and community-building, in which cognition and ethics constitute two inseparable dimensions of the mature presence of Christians in the media. The article concludes with seven findings and formative recommendations for media education and pastoral ministry in the context of digital culture. The remaining categories (relational, technical, and spiritual) will be discussed in a separate publication.